Correction to: Textile-Based Adsorption Sensor via Mixed Solvent Dyeing with Aggregation-Induced Emission Dyes (Materials, (2024), 17, 8, (1745), 10.3390/ma17081745) - Hong, Seong Gyun; Oh, Byeong M.; Kim, Jong H.; Lee, Jea Uk (Materials, 2024)
In the original publication [1], there was a small mistake in the molecular structure of Figure 1 and Figure 2, so it was corrected. The original figures will now be replaced by the following Figure 1 and Figure 2. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.